PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV DENGAN MATA PELAJARAN MATEMATIKA SD - Arina Rochmah Fadhila; Henry Aditia Rigianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Problem-Based Learning model on the critical thinking skills of fourth-grade elementary school students in mathematics at SD Negeri Suryodiningratan 3. This study is based on the low critical thinking skills of students and their preparation for the future. Through the application of the PBL model, it is hoped that students will be more active, critical, and directly involved in solving contextual problems related to everyday life. The method used in this study was a quantitative method with a quasi-experimental design. This design involved two groups, namely the experimental class and the control class as a comparison. The research instruments used included pretest and posttest descriptive tests and observation sheets of students' critical thinking activities compiled based on critical thinking indicators and PBL syntax. The sampling technique used purposive sampling, and data analysis was carried out through normality, homogeneity, and independent t-tests. The results of the study indicate that the Problem-Based Learning model has a significant effect on students' critical thinking skills. Based on the t-test results, a significance value of 0.002 ≤ 0.05 was obtained, which means that there is a difference in the mean between the experimental class and the control class. The average score of the experimental class increased from 45.93 to 83.24, while the control class increased from 42.93 to 77.24. Then, the Sig. (2-tailed) value was 0.001< 0.005, which means that H0 is rejected and H1 is accepted. This proves that the application of Problem Based Learning is more effective in improving students' critical thinking skills.